PENGARUH KAPASITAS SUMBER DAYA MANUSIA, PENGENDALIAN INTERN AKUNTANSI, DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KETEPATWAKTUAN PELAPORAN KEUANGAN - Prayitno Basuki; Endar Pituriningsih; Ahmad Rifa'i (Valid: Jurnal Ilmiah, 2016)
The purpose of this study are: 1) to examine the effect of human resources capacity to the timeliness of financial reporting, 2) to examine the effect of internal control in accounting to the timeliness of financial reporting, and 3) to examine the effect of information technology utilization to the timeliness of financial reporting. The population of this study is Satuan Kerja Perangkat Daerah (SKPD) on Local Government in Mataram totalled 36 SKPD consisting of the Department, Board, Office, and Inspectorat. Respondents in this study are the official financial administration and accounting staff who make the financial reporting on SKPD, which amounted to 72 (36 SKPD x 2), and of these, questionnaires were returned and can be processed by 60 questionnaires. Inferential statistical analysis techniques used are multiple regression analysis techniques, by F-test and t-test. The result showed that: human resources capacity (X1) effects to the timeliness of financial reporting (Y) (studies on SKPD in Mataram), internal control in accounting (X2) does not affect to the timeliness of financial reporting (Y) (studies on SKPD in Mataram), and information technology utilization (X3) affects to the timeliness of financial reporting (Y) (studies on SKPD in Mataram)